Minimally invasive spinal surgery for the management of symptomatic spinal metastasis. (3rd September 2017) - Hamad, Abdulkader; Vachtsevanos, Leonidas; Cattell, Andrew; Ockendon, Matthew; Balain, Birender
Abstract: Introduction: Symptomatic metastatic spinal disease is on the increase. Minimally invasive spinal surgery has been associated with a lower complication profile when compared to traditional open methods; however there is paucity of literature evaluating the place of percutaneous pedicle screw fixation (PPSF) in the management of spinal metastases. The purpose of the study is to assess the efficacy of Minimally Invasive Spine Surgery (MISS) using PPSF with or without mini-decompression in the management of symptomatic spinal metastases. Material and Methods: This is a single institution prospective study of 51 consecutive patients with metastatic spinal disease treated with PPSF. Patients presenting with pathological compression fractures and mechanical instability had PPSF, and those with radiological and/or clinical metastatic spinal cord compression (MSCC) underwent an additional mini-decompression. Data collected included patient demographics, Karnofsky's performance status (KPS), pain scores and neurology. Other data included number and location of involved levels, number of instrumented levels, blood loss, accuracy of screw placement and complications. Results: Of the 51 patients, 49 could be successfully treated with MISS (26 females and 23 males). 26 patients (55%) required a mini-decompression. 27 patients (55%) had improvement in KPS by at least 10 points ( p  < 0.0005). Only 2 patients (4%) had a worsening of KPS, due to other coexisting problems. Six of the 13 patients improved their neurology by one Frankel grade following surgery and 95% reported improvement in pain. Mean blood loss was 92mls for the fixation only group and 222mls for those requiring mini-decompression, with no other differences between these two surgical groups. Screw positioning was excellent in 91%, with 98% having uncompromised bony hold. Only two patients required revision surgery for aseptic loosening. Conclusion: MISS using PPSF is a safe and reproducible technique that maintains or improves functional outcome in the vast majority of patients presenting with spinal metastases.